Cystic Fibrosis Transmembrane Conductance Regulator Gene Abnormalities in Patients with Asthma and Recurrent Neutrophilic Bronchitis. Issue 1 (2012) - Goodwin, Jodi; Spitale, Naomi; Yaghi, Asma; Dolovich, Myrna; Nair, Parameswaran
Abstract : The present case series describes four patients with asthma, airway hyper-responsiveness and neutrophilic bronchitis who harboured abnormal cystic fibrosis transmembrance conductance regulator ( CFTR ) gene mutations. It serves both to alert clinicians to consider CFTR-related disease in both young and elderly patients with persistent neutrophilic bronchitis, and to highlight the potential utility of future genetic testing for CFTR abnormalities in patients with asthma and recurrent bronchitis or pansinusitis, and the role of nebulized hypertonic saline as a therapeutic option in these patients.